Improving Glycated Hemoglobin Control in a Rural Filipino Community: The Influence of Medication, Nutrition, and Lifestyle Counseling on Type 2 Diabetes Mellitus Patients - Ma. Danica Ines-Ramil; Rhian Jaymar Ramil; Esther Faith Gabriel; Learni Magdalena Bautista (Masters Program in Public Health, 2024)
Background: The Philippines is experiencing a growing diabetes prevalence in line with global patterns, despite free diabetes medications available at Rural Health Units (RHUs). This rise could be linked to factors like insufficient awareness and ability to self-manage the illness resulting in medica-tion non-adherence, negatively affecting patients’ health outcomes. The study aimed to evaluate the impact of counseling on glycated hemoglobin levels among Filipino diabetic patients in rural settings.Subjects and Method: A quasi-experimental research design was employed to determine the effect of one-on-one counseling on nutrition, lifestyle, and medication management on the HbA1C levels of the participants in a rural setting. A purposive sampling technique was used, and participants were selected based on predefined inclusion and exclusion criteria. Out of 60 diabetic patients enrolled in the study from Sinait RHU, 34 patients were qualified and randomly assigned into ‘test’ and ‘control’ groups (n=16). The ‘test’ group (n=18) received monthly counseling sessions lasting 20 to 25 minutes each, during monthly home visits for 3 months. Data on HbA1c reductions were compared using an unpaired t-test.Results: After 3-month counseling interventions, HbA1c level in the test group (Mean=6.38; SD= 1.21) was lower than the control group (Mean=9.27; SD=1.38) and it was statistically significant (p= 0.010). A substantial decrease in the HbA1c levels was observed in the test group whereas a significant increase was noted in the control group.Conclusion: The study’s findings suggest that counseling can help improve diabetic patients' perceptions of disease, diet, and lifestyle changes, resulting in better glycemic control and, ultimately, a higher quality of life. Keywords:HbA1c, Type 2 diabetes, nutrition counseling, medication counseling, lifestyle counseling, Philippines